A fatal case of Ecthyma Gangrenosum in a critically ill and immunocompromised patient - Marija Tomanovic; Vesna Reljic; Jelena Peric; Dubravka Zivanovic (Journal of Infection in Developing Countries)
Introduction: This brief picture-oriented case report focuses on typical skin lesions in a patient who developed Ecthyma gangrenosum and pseudomonal sepsis after extensive immunosuppressive therapy for Pemphigus vulgaris.